A Study of Living State Problems and Needs of Adaption, Habitation, and Co-Learning for Cultural Diversity Acceptance of Industrial Workers - Yimserhthi, Nathavy; Ratana-Ubol, Archanya; Kimpee, Pan (Journal of Education Studies, Chulalongkorn University, 2021)
The objectives of this research were to study living state, problems and needs of adaptation, habitation and co-learning for cultural diversity acceptance of industrial workers. The researcher conducted the study by inquiring 30 Thai industrial stakeholders and 400 Myanmar, Lao and Cambodian industrial workers in the North, the Central Part, the Northeastern and the South of Thailand. Questionnaire was used as research tool. It was found that most workers were female and their incomes were paid daily based on the minimum wage rate. The cause of their relocation was job dissatisfaction. On their free time, they play sports, watched movies and went sightseeing. The problems of language, food and friends from different localities made them feel uncomfortable when they first came to Thailand. They made friends with co-workers through small talking. From the research, self-adaptation modes of these workers were 1) adapting to foreign friends 2) communicating with colleagues 3) dressing appropriately 4) making friends confidently with foreigners, and 5) blending in with foreigners awkwardly. As for cohabitation, they had problems of 1) dependency 2) working with foreign co-workers 3) helping foreign friends 4) order of habitation and 5) appropriate dressing. As for the foreign culture, they had problems on learning 1) alienated behaviors and 2) alienated foods culture.